+0  
 
0
114
2
avatar

(sec(x)-1) * (sec(x)+1)* cot(x) = tan(x)

Guest Jun 13, 2017
Sort: 

2+0 Answers

 #1
avatar
+1

use the identity (a+b)(a-b) = a^2  - b^2  with {(sec x)-1}{ (sec x +1) }   to get

sec^2(x)  -  1

we can now write expression as

{sec^2(x) -1} * cot (x)    

and use the trig identity  sec^2(x) - 1   = tan^2(x)    to get expression as

tan^2(x)*cot(x)   = tan^2(x) * {1/tan(x)}     = tan(x)

Guest Jun 13, 2017
 #2
avatar+6810 
+2

\(\text{LHS}\\ =(\sec x - 1)(\sec x + 1)(\cot x) \\ =(\sec^2 x - 1)(\cot x)\\ =(\tan^2 x)(\cot x)\\ =\tan x\\ =\text{RHS}\)

MaxWong  Jun 13, 2017

11 Online Users

avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details